2021
DOI: 10.1007/s11205-021-02606-w
|View full text |Cite
|
Sign up to set email alerts
|

A Distributional Analysis of Uni-and Multidimensional Poverty and Inequalities in Ethiopia

Abstract: This study analyzes uni-and multidimensional poverty and inequalities in rural and small towns in Ethiopia. Unlike the unidimensional measure, the multidimensional measure of poverty shows all the channels through which poverty may manifest itself; it also shows the extent of deprivation. The analysis uses 6 dimensions with 14 indicators to construct a multidimensional index of poverty and inequalities using Ethiopian Households’ Socioeconomic Survey dataset. The study also uses multiple correspondence analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 64 publications
0
19
0
Order By: Relevance
“… 15 , 19 , 37 It could be a proxy for wealth because it reflects increased access to foods purchased outside the household. 38 We also found that child dietary diversity is significantly associated with maternal education. Similar findings have been reported by other studies.…”
Section: Discussionmentioning
confidence: 52%
“… 15 , 19 , 37 It could be a proxy for wealth because it reflects increased access to foods purchased outside the household. 38 We also found that child dietary diversity is significantly associated with maternal education. Similar findings have been reported by other studies.…”
Section: Discussionmentioning
confidence: 52%
“…This might be because productive lands for farming are usually located remotely from the smallholder's homestead. Thus, as Bersisa and Heshmati ( 2021 ) put it, reduced farm distance is associated with improved crop productivity and makes households less vulnerable to food poverty.…”
Section: Resultsmentioning
confidence: 99%
“…Studies that address this perspective have become popular because they focus on more general aspects of well-being (consumption, food security, health, education, labour rights, and human dignity) (Alkire et al, 2021). This vast literature on the determinants of multidimensional poverty has been used with greater emphasis to examine poverty levels in L&MICs, such as Ethiopia (Bersisa & Heshmati, 2021), Nigeria (Olarinde et al, 2020), Cameroon (Gautam et al, 2021), Brazil (Medeiros et al, 2021), and Bangladesh (Lázár et al, 2020). For example, Bersisa and Heshmati (2021) showed that demographic and regional characteristics influence household poverty levels in Ethiopia.…”
Section: Multidimensional Approachmentioning
confidence: 99%
“…This vast literature on the determinants of multidimensional poverty has been used with greater emphasis to examine poverty levels in L&MICs, such as Ethiopia (Bersisa & Heshmati, 2021), Nigeria (Olarinde et al, 2020), Cameroon (Gautam et al, 2021), Brazil (Medeiros et al, 2021), and Bangladesh (Lázár et al, 2020). For example, Bersisa and Heshmati (2021) showed that demographic and regional characteristics influence household poverty levels in Ethiopia. In Bangladesh, Lázár et al (2020) found that long-term reductions in structural poverty are caused mainly by the stability and performance of livelihoods, while the households that remain in poverty are those that experience high seasonality in their income and are involved in small-scale activities.…”
Section: Multidimensional Approachmentioning
confidence: 99%